Malthus - Evelyn, Frederick G. (Dublin Statistical Society, 1855)
As the present age is honourably distinguished by efforts, well-meant, though not unfrequently misdirected, to ameliorate the condition of the labouring classes; as I believe an all-important step in that direction to be a general acquiescence in the soundness of the views enunciated by Malthus, in his "Essay on Population" and as those views, having encountered a fierce opposition on their first promulgation, have been recently assailed by Mr. Rickards, Professor of Political Economy in the University of Oxford, and are habitually disposed of in a parenthesis at meetings of this Society, by two of its most distinguished members, Drs. Lawson and Hancock, under the complimentary designation of "that exploded fallacy" or "exploded Malthusianism" - in the teeth of the fact that the names of the two first of living British Economists, Mill and Senior, are inscribed on the Malthusian banner - under these circumstances, I feel no apology to be necessary for soliciting your attention, while I endeavour to point out (1.) what the theory of Malthus is; (2.) its evidence; (3.) its practical importance; and, (4.) finally, the attempts that have been made to impugn its truth.
Read 18th June, 1855
Keywords: Malthusianism; Malthus; 314.15